Identification of putative regulatory signals including the HAP1 binding site in the upstream sequence of the Aspergillus nidulans cytochrome c gene (cycA). - L J Johnson; R E BRADSHAW (Fungal Genetics Reports, 1998)
We speculate that a HAP1-like protein, similar to those which regulate oxygen transcriptional activation of many yeast respiratory genes, will probably also regulate the A. nidulans cytochrome c (cycA) gene. As part of a study to investigate the significance of a putative HAP1 (Haem Activator Protein) binding site in the regulatory region of the cycA gene, routine sequencing revealed an error in the published sequence (Raitt et al. 1994 Mol. Gen. Genet. 242: 17-22). Examination of the corrected sequence, including RT-PCR analysis of cycA mRNA, showed that an extra intron was present, and that the published translational start site was incorrect. This meant that the putative HAP1-binding site proposed by Raitt et al. could not be a regulatory element. However, further sequence analysis of the upstream sequence of the corrected cycA gene revealed putative regulatory signals, including possible HAP1 binding sites which are a closer match to recently reported yeast consensus sequences (Ha et al. 1996 Nucl. Acids Res. 24: 1453-1459).